Fabrication of poly (butadiene-block-ethylene oxide) based amphiphilic polymersomes : an approach for improved oral pharmacokinetics of Sorafenib - Muhammad Adeeb Khan (2020)
Sorafenib (SFN), a hydrophobic anticancer drug, has several limitations predominantly poor aqueous solubility and hepatic first-pass effect, limiting its oral delivery that results into several other complications. Present study aims to develop Sorafenib loaded polymersomes using poly butadiene block poly ethylene oxide (PB-b-PEO), an amphiphilic co-block polymer. Prior to drug loading, critical aggregate concentration (CAC) of polymer was calculated for stable formulation synthesis. The developed SFN loaded PB-b-PEO polymersomes (SFN-PB-b-PEO, test formulation) characterized by DLS and cryo-TEM showed particle size 282 nm, polydispersity (PDI) of less than 0.29 and membrane thickness of about 20 nm. SFN-PB-b-PEO polymersomes demonstrated encapsulation efficiency of 71% and showed sustained drug release up to 144 h. Formulation remained stable for 3 months in suspension form. In vitro cytotoxicity against HepG2 cells showed 1.7 folds improved toxicity compared to SFN suspension. In addition, oral administration of SFN-PB-b-PEO polymersomes in BALB/c mice showed increased Cmax and AUC0-96 by 1.7 and 2.77-fold respectively (p < 0.05) compared to those of SFN suspension (reference formulation). Findings suggest that the SFN-PB-b-PEO polymersomes can be a potential candidate for oral delivery of SFN.